The role of web-based flipped learning in EFL learners’ critical thinking and learner engagement - Pang, Ya (Frontiers in Psychology, 2022)
The flipped learning approach with the use of social media as an emerging technology has changed the quality of learning in English as a Foreign Language (EFL) educational contexts. This review probed the effect of the web-based flipped learning approach on learners’ engagement and critical thinking. The earlier studies revealed the significance of social media in developing learner engagement and critical thinking. Studies indicated that the provision of opportunities for more cooperative and collaborative learning activities, and high-quality interaction through the use of social media can be influential in developing learners’ engagement. Moreover, social media platforms can provide a context for feedback, and various types of challenging tasks that can improve EFL learners’ critical thinking. However, this review implicated that social media in flipped learning approach may be beneficial for language instructors, EFL teachers, teacher educators, educational policy-makers, and advisors to be aware of this valuable learner-centered approach.